Impact of high Fe-concentrations on microbial community structure and dissolved organics in hydrothermal plumes: an experimental study - Hansen, Christian T.; Kleint, Charlotte; Böhnke, Stefanie; Klose, Lukas; Adam-Beyer, Nicole; Sass, Katharina; Zitoun, Rebecca; Sander, Sylvia G.; Indenbirken, Daniela; Dittmar, Thorsten; Koschinsky, Andrea; Perner, Mirjam (Scientific reports, 2022)
Iron (Fe) is an essential trace element for life. In the ocean, Fe can be exceptionally scarce and thus biolimiting or extremely enriched causing microbial stress. The ability of hydrothermal plume microbes to counteract unfavorable Fe-concentrations up to 10 mM is investigated through experiments. While Campylobacterota ( Sulfurimonas ) are prominent in a diverse community at low to intermediate Fe-concentrations, the highest 10 mM Fe-level is phylogenetically less diverse and dominated by the SUP05 clade (Gammaproteobacteria) , a species known to be genetically well equipped to strive in high-Fe environments. In all incubations, Fe-binding ligands were produced in excess of the corresponding Fe-concentration level, possibly facilitating biological Fe-uptake in low-Fe incubations and detoxification in high-Fe incubations. The diversity of Fe-containing formulae among dissolved organics (SPE-DOM) decreased with increasing Fe-concentration, which may reflect toxic conditions of the high-Fe treatments. A DOM-derived degradation index (I DEG ) points to a degradation magnitude (microbial activity) that decreases with Fe and/or selective Fe-DOM coagulation. Our results show that some hydrothermal microbes (especially Gammaproteobacteria) have the capacity to thrive even at unfavorably high Fe-concentrations. These ligand-producing microbes could hence play a key role in keeping Fe in solution, particularly in environments, where Fe precipitation dominates and toxic conditions prevail.